Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(6x^2-xy-y^2\)
\(=6x^2-3xy+2xy-y^2\)
\(=3x\left(2x-y\right)+2y\left(x-y\right)\)
\(=\left(3x+2y\right)\left(x-y\right)\)
b, \(8x^2-23x-3\)
\(=8x^2-24x+x-3\)
\(=8x\left(x-3\right)+\left(x-3\right)=\left(8x+1\right)\left(x-3\right)\)
c, \(10x^2-11x-6\)
\(=10x^2-15x+4x-6\)
\(=5x\left(2x-3\right)+2\left(2x-3\right)\)
\(=\left(5x+2\right)\left(2x-3\right)\)
d, \(x^3-6x^2+11x-6\)
\(=x^3-3x^2-3x^2+9x+2x-6\)
\(=x^2\left(x-3\right)-3x\left(x-3\right)+2\left(x-3\right)\)
\(=\left(x^2-3x+2\right)\left(x-3\right)\)
\(=\left(x^2-2x-x+2\right)\left(x-3\right)\)
\(=\left(x-1\right)\left(x-2\right)\left(x-3\right)\)
a)
\(x^3+6x^2+11x+6=(x^3-x)+(6x^2+12x+6)\)
\(=x(x^2-1)+5(x^2+2x+1)\)
\(=x(x-1)(x+1)+6(x+1)^2\)
\(=(x+1)[x(x-1)+6(x+1)]=(x+1)(x^2+5x+6)\)
\(=(x+1)(x^2+2x+3x+6)\)
\(=(x+1)[x(x+2)+3(x+2)]=(x+1)(x+2)(x+3)\)
b) \(x^3+6x^2-13x-42\)
\(=x^3+2x^2+4x^2+8x-21x-42\)
\(=x^2(x+2)+4x(x+2)-21(x+2)\)
\(=(x+2)(x^2+4x-21)\)
\(=(x+2)[x^2-3x+7x-21)\)
\(=(x+2)(x+7)(x-3)\)
c)
\(x^3-5x^2+8x-4=(x^3-x^2)-4x^2+8x-4\)
\(=x^2(x-1)-4(x^2-2x+1)\)
\(=x^2(x-1)-4(x-1)^2\)
\(=(x-1)[x^2-4(x-1)]=(x-1)(x^2-4x+4)\)
\(=(x-1)(x-2)^2\)
d) \(2x^3-x^2+3x+6\)
\(=2x^3+2x^2-3x^2+3x+6\)
\(=2x^2(x+1)-3(x^2-x-2)\)
\(=2x^2(x+1)-3[x^2+x-2x-2]\)
\(=2x^2(x+1)-3[x(x+1)-2(x+1)]\)
\(=2x^2(x+1)-3(x+1)(x-2)\)
\(=(x+1)(2x^2-3x+6)\)
a)\(\left(x+1\right)\left(x+2\right)\left(x+3\right)\)
b)\(\left(x-3\right)\left(x-7\right)\left(x+2\right)\)
c)\(\left(x-3\right)\left(x+3\right)\left(x+2\right)\left(x+1\right)\)
d)\(\left(x+5\right)\left(x-3\right)\left(x+1\right)\left(x+2\right)\)
\(x^3+3.x^2.2+3.x.2^2+2^2-x+2=\left(x+2\right)^3-\left(x+2\right)=\left(x+2\right)\left(\left(x-2\right)^2-1\right)\)
x3+6x2+11x+6
= x3+3x2+3x2+9x+2x+6
=x2(x+3)+ 3x(x+3)+2(x+3)
=(x+3)(x2+3x+2)
a, \(x^4-6x^3+11x^2-6x+1=0\)
\(\Rightarrow\left(x^2-3x+1\right)^2=0\)
\(\Rightarrow x^2-3x+1=0\)
\(\Rightarrow x=\frac{\pm\sqrt{5}+3}{2}\)
Chúc bạn học tốt
\(x^4-\left(6x^2-2x^2\right)+\left(9x^2-6x+1\right)=0\)
\(x^4-2x^2\left(3x-1\right)+\left(3x-1\right)^2=0\)
\(\left(x^2-3x+1\right)^2=0\)
tự làm
B) \(\left(6x^4-18x^3\right)+\left(13x^{^3}-39x^2\right)+\left(x-3x\right)-\left(2x-6\right)=0\)
\(6x^3\left(x-3\right)+13x^2\left(x-3\right)+x\left(x-3\right)-2\left(x-3\right)=0\)
\(\left(x-3\right)\left(6x^3+13x^2-2\right)=0\)
\(\left(x-3\right)\left(6x^3+12x^2+x^2+2x-x-2\right)\)
\(\left(x-3\right)\left\{6x^2\left(x+2\right)+x\left(x+2\right)-\left(x+2\right)\right\}\)
\(\left(x-3\right)\left(x+2\right)\left(6x^2-x-1\right)\)
\(\left(x-3\right)\left(x+2\right)\left(6x^2-3x+2x-1\right)\)
\(\left(x-3\right)\left(x+2\right)\left(3x\left(2x-1\right)+\left(2x-1\right)\right)\)
\(\left(x-3\right)\left(x+2\right)\left(2x-1\right)\left(3x+1\right)=0\)
câu C nghĩ đã
a, \(x^4-6x^3+11x^2-6x+1=0\)
=> \(x^4-6x^3+9x^2+2x^2-6x+1=0\)
=> \(x^2+3x+1=0\)
=> \(\Delta\) =\(b^2-4c\)
=\(3^2.4=5\)
Nên \(\sqrt{\Delta}=5\)
x= \(\dfrac{-b+\sqrt{\Delta}}{2a}=\dfrac{-3+\sqrt{5}}{2}\)
hoặc x= \(\dfrac{b+\sqrt{\Delta}}{2a}=\dfrac{3+\sqrt{5}}{2}\)
a)
\(x^3-7x-6=x^3-x-6x-6\)
\(=x(x^2-1)-6(x+1)\)
\(=x(x-1)(x+1)-6(x+1)=(x+1)[x(x-1)-6]\)
\(=(x+1)(x^2-x-6)=(x+1)[x^2-3x+2x-6]\)
\(=(x+1)[x(x-3)+2(x-3)]=(x+1)(x+2)(x-3)\)
b) \(x^3-6x^2+8x\)
\(=x(x^2-6x+8)\)
\(=x(x^2-4x-2x+8)\)
\(=x[x(x-4)-2(x-4)]=x(x-2)(x-4)\)
c) \(x^4+2x^3-16x^2-2x+15\)
\(=(x^4+2x^3-x^2-2x)-15x^2+15\)
\(=[(x^4-x^2)+(2x^3-2x)]-15(x^2-1)\)
\(=[x^2(x^2-1)+2x(x^2-1)]-15(x^2-1)\)
\(=(x^2-1)(x^2+2x)-15(x^2-1)=(x^2-1)(x^2+2x-15)\)
\(=(x^2-1)(x^2-3x+5x-15)=(x^2-1)[x(x-3)+5(x-3)]\)
\(=(x^2-1)(x+5)(x-3)=(x-1)(x+1)(x+5)(x-3)\)
d)
\(x^3-11x^2+30x=x(x^2-11x+30)\)
\(=x(x^2-5x-6x+30)\)
\(=x[x(x-5)-6(x-5)]=x(x-6)(x-5)\)
\(x^3+6x^2+11x+6=x^3+x^2+5x^2+5x+6x+6\)
\(=x^2\left(x+1\right)+5x\left(x+1\right)+6\left(x+1\right)=\left(x+1\right)\left(x^2+5x+6\right)\)
\(=\left(x+1\right)\left(x^2+2x+3x+6\right)=\left(x+1\right)\left[x\left(x+2\right)+3\left(x+2\right)\right]\)
\(=\left(x+1\right)\left(x+2\right)\left(x+3\right)\)
\(x^3-6x^2+11x-6\)
\(=x^2\left(x-1\right)-5x\left(x-1\right)+6\left(x-1\right)\)
\(=\left(x-1\right)\left(x^2-5x+6\right)\)
\(=\left(x-1\right)\left(x-2\right)\left(x-3\right)\)